STUDI KOMPARASI ANTARA PENGGUNAAN METODE MIND MAPDAN METODE CERAMAH DAN IMPLIKASINYA TERHADAP MINAT BELAJAR SISWA KELAS VIIDI SMP 2MAKALE, TANA TORAJA - Fery Kotok; Alfian Bonggalangi’; Enjelina Enjelina (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This title was raised to find out the implications of using the Mind Map Method and Lecture Method on the of Class VII Students at SMP 2 Makale, Tana Toraja. Learning is a process that involves carrying out activities and experiencing, remembering, to arrive at a goal to be achieved. Because in the teaching and learning process the method used is only the lecture method so that when students receive material from the teacher they do not pay proper attention to the teacher, but instead go in and out of the classroom, make noise in class, scribble on books, and other things. The mind map method is a technique for recalling and storing information in the brain based on associations/imagination and the lecture method is a form of explanation given orally for an idea, which is adjusted to the facts. Usually, if there is still time, it will be closed with a question and answer activity by the teacher to the students and/or students to the teacher.